MENINGKATKAN KUALITAS PROSES PEMBELAJARAN DAN KEMAMPUAN MENULIS CERITA DENGAN MODEL ASSURE - Winda Ayu Cahya Fitriani (Universitas PGRI Madiun, 2016)
This research aims to improve learning quality and ability for writing story in Muhammadiyah 11 Surakarta Elementary School by applying ASSURE model. The method uses classrom research, which was carried on for five months. The subject of this research fifth grade elementary school in Muhamadiyah 11 Surakarta, which consists of 31 students. The teacher and the student is the source of the data. The techniques used for collecting data are observation, interview, angket, and test. Data source and triangulation uses to ensure the validity. Analyzing data comparative descriptive analysis techniques is used. The result of the research proves learning process cycles I in story writing achieve 60% better than pra research, which achieve less 35%. In cycles II learning process increase get 80%. This research conclute that implementing the learning model of ASSURE is capable of increasing the quality of learning process and students ability for writing story in Muhamadiyah 11 Surakarta fifth grade elementary school.